Le Hall d’exposition de l’aéroport du Bourget - Hélène Caroux (In Situ)
If the international airshow held at Le Bourget every two years is relatively familiar, the architectural history of the 1953 exhibition hall specially built at the southernmost tip of the airfild site is less well known. Opened for the twentieth international airshow, on the first ocasion it was held at Le Bourget, it bears witness to the whole history of these airshows, first organised in Paris fifty years earlier. It is also an emblematic creation in the career of the architect André Granet, a fervent defender of all things aeronautical. He was one of the founders of the GIFAS, the French association of air and space industries, and also one of the founders of the airshow itself, which he ran for almost fifty years. He was first appointed organiser of the 'salon' in 1909 when the event was held in the Paris Grand Palais. After the Second World War, the development of aviation and the progress in aircraft design rendered this venue (built for the 1900 exhibition) too small and inappropriate. The airshow was also meeting with ever greater public enthusiasm. It was decided then to move the airshow to the site of the Bourget airport in a permanent, modern and functional building. The building's design comprised a semi-circular main hall with two wings, evoking those of an aeroplane. It was only a few years later, however, that the new exhibition hall achieved its final form. It has since been completed by other exhibition pavilions, and the structure itself is now invisible beneath a uniform metallic cladding. The hall was the venue for the 2015 Paris conference on climate change and will be used as a media centre for the Olympic and paralympique games planned for 2024.